Association of coexisting anti-ribosomal P and anti-dsDNA antibodies with histology and renal prognosis in lupus nephritis patients. (March 2021) - Wakamatsu, Ayako; Sato, Hiroe; Kaneko, Yoshikatsu; Cho, Takamasa; Ito, Yumi; Kurosawa, Yoichi; Hasegawa, Eriko; Kobayashi, Daisuke; Nakatsue, Takeshi; Kuroda, Takeshi; Suzuki, Yoshiki; Uchiumi, Toshio; et al.
Objectives: Anti-ribosomal P protein autoantibodies (anti-P) specifically develop in patients with systemic lupus erythematosus. Associations of anti-P with lupus nephritis (LN) histological subclass and renal outcome remain inconclusive. We sought to determine the association of anti-P and anti-double-stranded DNA antibody (anti-dsDNA) with renal histology and prognosis in LN patients. Methods: Thirty-four patients with LN, having undergone kidney biopsy, were included. The 2018 revised ISN/RPS classification system was used for pathophysiological evaluation. Chronic kidney disease (CKD) was defined as an estimated glomerular filtration rate < 60 mL/min/1.73 m 2 for > 3 months. Results: Six patients (17.6%) were positive for anti-P and 26 (76.5%) for anti-dsDNA. Among the six patients with anti-P, one did not have anti-dsDNA, but did have anti-Sm antibody, and showed a histological subtype of class V. This patient maintained good renal function for over 14 years. The remaining five patients, who had both anti-P and anti-dsDNA, exhibited proliferative nephritis and were associated with prolonged hypocomplementemia, and the incidence of CKD did not differ from patients without anti-P. Conclusion: Although this study included a small number of patients, the results indicated that histology class and renal prognosis associated with anti-P depend on the coexistence of anti-dsDNA. Further studies with a large number of patients are required to confirm this conclusion.